Never social and entrepreneurial enough? Exploring the identity work of social entrepreneurs from a psychoanalytic perspective. (November 2017) - Driver, Michaela
Building on an analysis of interviews with 61 social entrepreneurs, the study offers a more fine-grained exploration of the identity work of social entrepreneurs from a psychoanalytic, particularly Lacanian, perspective. Specifically, it suggests that what defines social entrepreneurial identity work is the blurring of beatific and horrific aspects of fantasies and a desire for struggle and lack. This in turn creates an emancipatory space in which discursive movement enables alternative forms of market enjoyment and ethical agency. The latter unsettles macro-discourses of capitalism by demanding and amplifying their lack. The study contributes new avenues for exploring Lacanian concepts such as the traversal of fantasy as a product of discursive movement particularly relevant for transformative readings of identity narratives.